Persepsi Konsumen Terhadap Kualitas Pelayanan Wedding Event Di Amankila Resort Karangasem, Bali - Sawitri, Hari; Wirata, I Nengah; Suprastayasa, I Gusti Ngurah Agung (Journal of Event and Convention Management, 2024)
Consumer perception is important in the company. Consumer perception can be influenced by several factors, one of them is service quality. The purpose of this study was to determine the consumer perception towards wedding event quality services at Amankila Resort. The sample in this research are 32 respondents, which Amankila Resort wedding event consumers in period of time 2019 – 2022. This study used a quantitative descriptive analysis technique with SPSS version 25 through validities test and reliabilities test. Data collection techniques used are surveys, observation and documentation studies. Based on the results of the analysis, it was found that regarding consumer perceptions towards wedding event service quality at Amankila Resort are considered very good with an average value of 4.48. The dimension of service quality that has the highest average value of 4.65 is the empathy dimension, while the dimension of service quality that has the lowest average value of 3.4 is the tangibles dimension.